MICROBIOLOGICAL QUALITY OF IMPORTED FROZEN FISH FILLETS IN KOSOVAR MARKETS - UKA, Albana (International Journal of Research -GRANTHAALAYAH, 2022)
Fish meat is a good source of nutritional value, but due to rapid and possible microbial contamination, it can pose a high risk to the health of consumers. In this study, 43 samples of imported fish frozen meat, which were collected in the markets of Prishtina, Kosovo, were analyzed. The microbiological parameters that are used are Escherichia coli, Salmonella, Listeria monocytogenes, and Vibrio cholerae. In the last three parameters, we have no detections in all samples. The exception is Escherichia coli, appearing in 85% of the analyzed samples with values <10 CFU/g. This contamination is likely from poor hygienic practices of the workers during the process of processing the fish fillet and presence of can cause severe foodborne disease.